Natural resource conflicts and community organizations in Bangladesh - Sultana, Parvin; Thompson, Paul M. (International Food Policy Research Institute, 2013)
This analysis assesses community based organization (CBO) performance including conflict management over three years among about 150 floodplain CBOs and reviews experience in the five forest protected areas with co-management.